SHARIA INTERNAL RESOURCES: CAPABILITIES TO DRIVE THE SUSTAINABILITY OF ISLAMIC BANKING - Thaib, Irwan; Puspaningrum, Astrid; Hussein, Ananda Sabil; Prabandari, Sri Palupi (Islam Futura, 2025)
Having the largest Muslim population in the world, Indonesia presents a potential market for the development of Islamic banking, especially considering that the market share of Islamic banking is currently less than 10%. The unique characteristics of Islamic banking, which distinguish it from conventional banking, suggest the possibility of having extraordinary internal resource capabilities. This study aims to explore internal resources within the context of Islamic banking, a sector with considerable potential for growth in the financial industry. This study uses an exploratory approach with focus group discussion and exploratory factor analysis to develop and identify the dimensions of Sharia Internal Resources. The results are first-order factors generated by grouping items into four dimensions. Each formed dimension corresponds to Islamic elements that refer to activities and operational processes based on Islamic law. Furthermore, the second-order analysis found that the formed, first-order factors can be integrated into a more comprehensive construct: Sharia Internal Resources. These findings enrich general knowledge by providing insight into the internal resources that are essential and unique for the sustainability of the Islamic banking sector, particularly when facing competition dominated by conventional banking.